Fast Cyclization of a Proline‐Derived Self‐Immolative Spacer Improves the Efficacy of Carbamate Prodrugs. (22nd January 2020) - Dal Corso, Alberto; Borlandelli, Valentina; Corno, Cristina; Perego, Paola; Belvisi, Laura; Pignataro, Luca; Gennari, Cesare
Abstract: Self‐immolative (SI) spacers are sophisticated chemical constructs designed for molecular delivery or material degradation. We describe herein a ( S )‐2‐(aminomethyl)pyrrolidine SI spacer that is able to release different types of anticancer drugs (possessing either a phenolic or secondary and tertiary hydroxyl groups) through a fast cyclization mechanism involving carbamate cleavage. The high efficiency of drug release obtained with this spacer was found to be beneficial for the in vitro cytotoxic activity of protease‐sensitive prodrugs, compared with a commonly used spacer of the same class. These findings expand the repertoire of degradation machineries and are instrumental for the future development of highly efficient delivery platforms. Abstract : Eine Frage der Zeit : Die schnelle Cyclisierung eines von Prolin abgeleiteten selbstzerlegenden Spacers führt zur Spaltung von ansonsten stabilen Carbamaten und der effizienten Freisetzung hydroxyhaltiger Wirkstoffe. Diese beschleunigte Wirkstofffreisetzung erhöht in vitro die Antikrebsaktivität von Modell‐Prodrugs im Vergleich zu einem bekannten Spacer der gleichen Klasse.